Impact of unipolar voltage criteria for left atrial posterior wall on atrial fibrillation recurrence after pulmonary vein isolation. (26th March 2023) - Watanabe, Tomonori; Watanabe, Hiroaki; Hachiya, Hitoshi; Sato, Masafumi; Mitama, Tadayuki; Okuyama, Takafumi; Yokota, Ayako; Kamioka, Masashi; Komori, Takahiro; Kabutoya, Tomoyuki; Imai, Yasushi; Kario, Kazuomi
Abstract: Introduction: Beyond pulmonary vein isolation (PVI), additional therapeutic strategies for atrial fibrillation (AF) have not been established. Remodeling of the left atrium (LA) could impact AF recurrence post‐PVI. We investigated the impact of unipolar voltage (UV) criteria for the LA posterior wall (LA‐PW) on AF recurrence post‐PVI. Methods: We reviewed the cases of 106 AF patients (mean age 63.8 years, nonparoxysmal AF: 59%) who underwent extensive encircling PVI by radiofrequency ablation guided by a 3‐dimension mapping system, investigating the impact on AF recurrence of the UV criteria of the LA. Results: Out of all patients, 26 patients had AF recurrence during post‐PVI follow‐up [median 603 days]. They showed a higher percentage of nonparoxysmal AF (80.8 vs. 52.5%, p  = .011), longer AF duration (2.9 ± 2.7 vs. 1.0 ± 1.7 years, p  = .002), and larger area size of UV < 2.0 mV in LA‐PW (2.8 ± 1.8 vs. 1.0 ± 1.5 cm 2, p  < .001) than those without recurrence. Cox Hazard analysis for AF recurrence adjusted by age, gender, AF duration, body mass index and left atrial volume index revealed that an area size over 2.0 cm 2 of UV < 2.0 mV in LA‐PW (HR 6.9 [95% CI:1.3–35.5], p  = .021) posed independent risks for AF recurrence post‐PVI. The atrial arrhythmia‐free survival rate was higher in those with no area of UV < 3.0 mV in LA‐PW compared to those with a sizable area (>2.0 cm 2 ) of UV < 3.0 mV and <2.0 mV (95.0% vs. 74.2% vs. 57.1%, Log‐Rank: p  < .001). In the AF etiology of patients with AF recurrence, 9 of 14 patients who underwent the 2nd procedure had no PV reconnection, and 8 patients required the LA‐PW isolation for their non‐PV AF. Conclusion: UV criteria of LA‐PW is a useful parameter for AF‐recurrence post‐PVI. Lower UV in LA‐PW as an indication of electrical remodeling could indicate a higher risk of AF recurrence and the need for further therapeutic strategies. Abstract : A representative case exhibiting a serial change of LA remodeling. Pre‐voltage mapping at the 1st procedure before PVI showed no low voltage area in bipolar voltage mapping (left upper panel) and a unipolar voltage area of 3.0 cm 2 of UV < 2.0 mV in LA‐PW (right upper panel). The patient underwent the only PVI. The patient had recurrence of AF after PVI. Voltage mapping at the 2nd procedure 7 months later indicated no PV reconnection and heterogeneous spread of low voltage area in LA‐PW (left lower panel). Area of UV < 2.0 mV was wider than the bipolar low voltage area of conventional criteria in LA‐PW. LA‐PW isolation for the non‐PV AF foci was needed to maintain sinus rhythm at the 2nd procedure. Patients were divided to three groups based on the voltage criteria in LA‐PW: (A) no area of UV < 3.0 mV, (B) area size over 2.0 cm 2 of UV < 3.0 mV, (C) area size over 2.0 cm 2 of UV < 2.0 mV. Group (B) did not include group (C): group (B) had the area size over 2.0 cm 2 of UV 2.0 mV≤ and <3.0 mV. Kaplan–Meier AF/AT free survival curve indicated that the AF/AT free survival rate of the patients with no area of UV < 3.0 mV in LA‐PW was significantly higher than those with area size over 2.0 cm 2 of UV < 3.0 mV or <2.0 mV in LA‐PW (95.0% vs. 74.2% vs. 57.1%, median follow‐up duration of 603 days, Log‐Rank (Mantel–Cox): p  < .001). AF, atrial fibrillation; AT, atrial tachycardia; PVI, pulmonary vein isolation; LA, left atrium; PW, posterior wall; UV, unipolar voltage.